Involvement of HIF-1 &HIF-2 in the hypoxic induction of VEGF and MMP-7 genes - البرغثي Laila; عزوز Lubna (مجلة العلوم الإنسانية والتطبيقية, 2016)
Aim: To describe the use of siRNA technology to inhibit HIF-1α and HIF-2α expression in primary macrophages cultured in vitro, to determine whether pro- MMP-7 expression is regulated by these two HIFs. In these experiments, the well described HIF-target, VEGF, is used as a positive control whenever possible. Methods: Monocytes were isolated from buffy coats & grown for seven days to be differentiated into MDM, then HIF-1 α, HIF-2α expression were inhibited by transfection with siRNA oligonucleotide, finally the expression of VEGF & MMP-7 were examined. Results: Complete inhibition of pro-MMP-7 & VEGF release by MDM showing that their hypoxic regulation is entirely dependent of HIF-1 and HIF-2. Conclusion: These findings indicate that both genes identified could be important for the survival and functioning of macrophages in hypoxic diseased tissues. Moreover, these data emphasize that the role of HIF-2α in addition to HIF-1α needs to be considered when developing agents that target the HIF pathway.